Novel Approaches in Chronic Renal Failure without Renal Replacement Therapy: A Review - Sandra Luz Martínez-Hernández; Martín Humberto Muñoz-Ortega; Manuel Enrique Ávila-Blanco; Mariana Yazmin Medina-Pizaño; Javier Ventura-Juárez (Biomedicines, 2023)
Chronic kidney disease (CKD) is characterized by renal parenchymal damage leading to a reduction in the glomerular filtration rate. The inflammatory response plays a pivotal role in the tissue damage contributing to renal failure. Current therapeutic options encompass dietary control, mineral salt regulation, and management of blood pressure, blood glucose, and fatty acid levels. However, they do not effectively halt the progression of renal damage. This review critically examines novel therapeutic avenues aimed at ameliorating inflammation, mitigating extracellular matrix accumulation, and fostering renal tissue regeneration in the context of CKD. Understanding the mechanisms sustaining a proinflammatory and profibrotic state may offer the potential for targeted pharmacological interventions. This, in turn, could pave the way for combination therapies capable of reversing renal damage in CKD. The non-replacement phase of CKD currently faces a dearth of efficacious therapeutic options. Future directions encompass exploring vaptans as diuretics to inhibit water absorption, investigating antifibrotic agents, antioxidants, and exploring regenerative treatment modalities, such as stem cell therapy and novel probiotics. Moreover, this review identifies pharmaceutical agents capable of mitigating renal parenchymal damage attributed to CKD, targeting molecular-level signaling pathways (TGF-β, Smad, and Nrf2) that predominate in the inflammatory processes of renal fibrogenic cells.